2022
DOI: 10.21608/ejmr.2022.267691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of administration of Tadalafil on Gentamicin-induced nephrotoxicity in rats

Abstract: Background: Gentamicin (GNT) is a highly effective aminoglycoside antibiotic that is commonly used to treat life-threatening bacterial infections. Aim: The aim of the current study is to determine whether tadalafil can protect against GNT-induced nephrotoxicity. Methods: Twenty-four male Albino rats were used in the study, which were randomly divided into four groups, six animals each.Control untreated group received distilled water (5ml/kg, P.O) for 12 days and on days 6-12, they received (5ml/kg,i.p) normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
3
1
0
Order By: Relevance
“…In agreement with this finding, TAD was reported to reduce both FBG and HbA1C% [ 33 ], as well as PTX did [ 34 ]. The effect of both drugs in improving kidney function was evident in the current study as indicated by the increase in Cr Cl & the decrease in S. Cr which is in line with other studies [ 35 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with this finding, TAD was reported to reduce both FBG and HbA1C% [ 33 ], as well as PTX did [ 34 ]. The effect of both drugs in improving kidney function was evident in the current study as indicated by the increase in Cr Cl & the decrease in S. Cr which is in line with other studies [ 35 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the group treated with TAD along with AmB showed reduced renal NO content, down-regulated iNOS, and up-regulated eNOS protein expression by comparison to AmB group. Parallel to our results, a previous study has demonstrated the protective of TAD agaist gentamicin-induced nephrotoxicity by regulating renal NO content and iNOS/eNOS expression (Mohammed et al, 2022 ). These regulatory effects of TAD could be partly attributed to its anti-inflammatory and antioxidant properties that attenuate NF-κB/iNOS signaling.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, pretreatment with TAD showed remarkable attenuation of oxidative damage in AmB-treated rats where renal MDA content was reduced while GSH content was elevated. These results are parallel to those of previous studies elucidating the nephroprotective effect of TAD against contrast-induced nephropathy, diabetic nephropathy, gentamicin-, and cisplatin-induced nephrotoxicity models via its antioxidant properties (Adeneye and Benebo, 2016 , Elhawary and Abd Allah, 2017 , Iordache et al, 2020 , Mohammed et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation